Uncommon lymphocytic leukemias in patients from the state of Zulia, Maracaibo, Venezuela. I. The coexpression of lymphocytes B-cell and T-cell markers in two patients with chronic lymphocytic leukemia - De Salvo Cardullo, L.; Weir Medina, J. E.; León, M.; Gómez, O. (Investigación Clínica, 2013)
In this report we describe the coexpression of T-and B-cell markers on Iymphocytes from two patients with B-cell, chronic Iymphocytic leukemia. The T-cell markers tested included the sheep red blood cell (SRBC) receptor and the T1 and T11 antigens; the B-cell markers included B4, B1, B2; and Dr (la); surface immunoglobulin IgM, IgD, IgG Kappa and lambda chains. Analysis of the results by independent multiplicative probability showed a minimum coexpression of T and B-markers on 18.83% and 29.15% of the cells from patients 1 and 2, respectively. Two findings stand out from the results reported here. First, the report documents two additional cases of this rare form of CLL. Second, the cases were detected in patients from the state of Zulia, Venezuela, where the incidence of chronic lymphocytic leukemia is low.